Success Factors for Academic Performance among Private Secondary Schools in Tanzania: A Case of Selected Schools in Dar Es Salaam, Morogoro and Coast Regions - Kusiluka, Moses Ayoub J (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2018)
The study sought to assess success factors for academic performance among private schools in Tanzania. The purpose of the study is to address the problem of declining academic performance in secondary school system. Most of the past studies have attributed this decline to limited availability of teaching staff and physical learning infrastructure. These studies examined the quantitative elements of school’s internal physical resources; little efforts were made to assess quality aspects of the resources and most of them studies were conducted in public schools, treating schools as public service rather than business entities. Furthermore, the theoretical approaches used in assessing secondary education problems in these studies were pedagogical as opposed to business theories which are more relevant to private schools. There is therefore limited knowledge on quality aspects of resources and business orientation of factors behind successful academic performance among private schools. The respondents of the study were school owners, managers, teachers, and students. Data collection instruments were interview checklists and questionnaires, complemented by documentary review and researcher’s observation. Data analysis revealed a number of factors contributing to successful school academic performance, namely, school factors, student factors and market or community factors. The study came out with conclusion that the academic performance among private schools in Tanzania depends much upon availability of internal resources (Resource Based View) complemented with improved service quality (Gronroos Service Quality Model). External resources played limited role. The study came up with a number of recommendations to school owners and the government: in additional improving school resources such as facilities, teachers and materials, schools should improve service quality; schools should use strategies that halt students’ vices which affect class-room attendance and concentration; they should match teachers, incentives with their socio-demographic attributes; they should incapacitate school heads with business management skills or recruit professional managers to manage schools rather than using teachers school heads; furthermore, low performing schools should improve owner-manager cooperation; the government should review ICT policy (2003) and enact strict laws to regulate ICT users; the government should not leave fee rates charged by private secondary school be determined by forces of demand and supply; it should also review teachers curricula to accommodate business management skills;